Knowledge Management For 21st Century Information Professionals - Jain, Priti (Journal of Knowledge Management Practice, 2009)
Due to rapidly changing information and communication technology (ICT), library science has been incessantly evolving. The internet has further transformed the information society into to a global society. The knowledge explosion and ICT tools have equipped information and library science with immediate access to practically limitless sources, plus quick storage, retrieval and sharing tools. In this knowledge economy age information professionals’ roles have therefore changed profoundly at both library practitioner and library school educator levels. On the library side information professionals have evolved from traditional cataloguer and research and reference service providers to value added service providers, teacher librarians and, most recently, knowledge managers. On the library school educators’ side, there is the constant challenge to review the curriculum, keep up to date and extend personal capacity according to the needs of the knowledge society. This paper looks particularly at the importance of knowledge management for 21st century information professionals; their evolving new roles, skills and challenges, and finally recommends what is important to have in place for information professionals to be part of this knowledge management economy.
Keywords: Librarians; Library school educators; Information professionals; Knowledge management